Data science for complex systems - Chakrabarti, Anindya S. (Cambridge University Press, 2023)
This text provides an accessible guide to the tools and techniques of data science that can be utilised for the analysis of complex systems. This text is an invaluable resource for scientists, engineers and social scientists who require effective analysis of large quantities of data.